Rancang Bangun Harga Pokok Proses Pada CV. Amin Rizkana - Yulia Yulia; Nanda Diaz Arizona (LPPM Universitas Bina Sarana Informatika, 2021)
CV. Amin Rizkana is a manufacturing company producing rosella-based tea. The production process still faces several obstacles, mainly related to the recording process for each operational activity, and the filing process is still done manually and has not been structured, namely the absence of accounting still relies only on memoranda that are archived in the map. So there is often a difference in arithmetic because there is no fixed record and archived notes are often lost and it is difficult to find transaction data. With the support of this accounting information technology system, manual and conventional data processing processes can be carried out effectively with a computerized system. The design of information systems with the Cost of Process method with a computerized system is the best solution. Every process of rosella flower tea production is recorded accurately so that it can provide real-time and valid data to support management in making strategic decisions. The author designs and implements the system using the Java Netbeans 8.1 Application Program, by making Account Codes, Recording Raw Materials, Labor Costs, Factory Overhead Cost (BOP) Allocation, Ledgers, and Cost of Production. Keywords: Design, Method of Cost of the Process, Java Netbeans 8.1